Electrochemical behavior of Sn-9Zn-xCu solder alloy in 3.5 wt% NaCl solution at room temperature - Jaiswal D.; Kumar S.; Behera C.K. (My University, 2025)
The effect of Cu addition on potentiodynamic and static immersion corrosion behavior of Sn-9Zn-xCu (x = 0,1,2,3 wt%) was evaluated for their application in the electronic industry. Samples of solder alloy were prepared through vacuum induction furnace melting. Techniques such as SEM, XRD, and XPS were applied to evaluate the morphology and corrosion products on the surface. Microstructural characterization and phase analysis before the corrosion test show the presence of Cu5Zn8 and Cu6Sn5 intermetallics in the matrix. The primary corrosion products were found to be zinc hydroxide chloride Zn5(OH)8Cl2·H2O, tin oxide chloride hydroxide (Sn3O(OH)2Cl2), SnO, and ZnO. The possible reasons for the generation of zinc corrosion products were critically discussed, and the most precise mechanism was proposed. Adding 1–3 wt% copper to the Sn-9Zn solder alloy increased its corrosion resistance, owing to coarser and more evenly distributed corrosion-vulnerable Zn-rich precipitates. Static corrosion tests show that the weight loss decreases with increased copper content, indicating an increase in corrosion resistance. Sn-9Zn-3Cu alloys recorded the maximum corrosion resistance among all the alloys in the above corrosion tests. © 2022 Elsevier Ltd